Assessment of Pain Expression in Infant Cry Signals Using Empirical Mode Decomposition - Mijović, B.; Silva, M.; Bergh, Van den B. R. H.; Allegaert, K.; Aerts, J. M.; Berckmans, D.; Huffel, Van S. (Methods of Information in Medicine, 2010)
Background:The presence of decoupling, i.e. the absence of coupling between fundamental frequency variation and intensity contour during phonetic crying, and its extent, reflects the degree of maturation of the central nervous system.Objectives: The aim of this work was to evaluate whether Empirical Mode Decomposition (EMD) is a suitable technique for analyzing infant cries. We hereby wanted to assess the existence and extent of decoupling in term neonates and whether an association between decoupling (derived from EMD) and clinical pain expression could be unveiled.Methods: To assess decoupling in healthy term neonates during procedural pain, 24 newborns were videotaped and crying was recorded during venous blood sampling. Besides acoustic analysis, pain expression was quantified based on the Modified Behavioral Pain Scale (MBPS). Fundamental frequency and the intensity contour of the cry signals were extracted by applying the EMD to the data, and the correlation between the two was studied.Results: Based on data collected in healthy term neonates, correlation coefficients varied between 0.39 and 0.83. The degree of decoupling displayed extended variability between the neonates and also in different cry bouts in a crying sequence within an individual neonate.Conclusion: When considering the individual ratio between the mean correlation of cry bouts during a crying sequence and their standard deviation, there seems to be a positive trend with increasing MBPS value. This might indicate that higher stressed subjects have less consistency in the investigated acoustic cry features, concluding that EMD has potential in the assessment of infant cry analysis.
Keywords: Empirical mode decomposition; phonetic crying; pain expression; neonates